Swedish women's perceptions of and conformity to feminine norms. Issue 3 (24th April 2017) - Kling, Johanna; Holmqvist Gattario, Kristina; Frisén, Ann
Abstract : The relatively high gender equality in the Swedish society is likely to exert an influence on gender role construction. Hence, the present research aimed to investigate Swedish women's perceptions of and conformity to feminine norms. A mixed methods approach with two studies was used. In Study 1, young Swedish women's gender role conformity, as measured by the Conformity to Feminine Norms Inventory 45 (CFNI‐45), was compared to the results from previously published studies in Canada, the United States, and Slovakia. Overall, Swedish women displayed less conformity than their foreign counterparts, with the largest difference on the subscale Sexual fidelity. In Study 2, focus group interviews with young Swedish women added a more complex picture of feminine norms in the Swedish society. For instance the results indicated that Swedish women, while living in a society with a strong gender equality discourse, are torn between the perceived need to invest in their appearances and the risk of being viewed as non‐equal when doing so. In sum, despite the fact that traditional gender roles are less pronounced in Sweden, gender role conformity is still a pressing issue. Since attending to the potential roles of feminine norms in women's lives previously has been proposed to be useful in counseling and therapeutic work, the present research also offers valuable information for both researchers and practitioners. [Correction added on 5 May 2017, after first online publication in April 2017: An incorrect Abstract was inadvertently captured in the published article and has been corrected in this current version.]